Janus Electrolyte with Modified Li+ Solvation for High‐Performance Solid‐State Lithium Batteries. (26th May 2022) - Hu, Yuzhen; Li, Linge; Tu, Haifeng; Yi, Xiaohong; Wang, Jian; Xu, Jingjing; Gong, Wenbin; Lin, Hongzhen; Wu, Xiaodong; Liu, Meinan
Abstract: Solid‐state lithium‐metal batteries attract great attention due to their high energy density and superior safety. However, the sluggish Li + kinetics of solid electrolyte and poor interface compatibility between electrolyte and lithium anode lead to unsatisfied performance at room temperature, which severely limit their practical application. Herein, a Janus quasi‐solid electrolyte (JSE) design is reported, which modifies the Li + solvation environment in succinonitrile (SN) plastic crystal electrolyte and creates 1D Li + transportation channels. Density functional theory calculations and Raman results reveal that Li1.3 Al0.3 Ti1.7 (PO4 )3 changes the Li + solvation environment from SN units to aggregated ion pairs, which accelerates the diffusion rate of Li + . As a result, JSE presents excellent ionic conductivity (0.73 mS cm −1 ) and high lithium transference number (0.72). With this efficient JSE, Li symmetric cells deliver excellent cycle stability over 600 h with a low over potential of 60 mV. LiFePO4 |JSE|Li solid‐state battery delivers an impressive performance with a specific discharge capacity of 152 mAh g −1 after 100 cycles at room temperature under 0.5 C. Moreover, the corresponding pouch cell also shows outstanding performance (140 mAh g −1 under 0.5 C) and withstands abuse tests such as bending and cutting, demonstrating its superior safety for future utilization. Abstract : A Janus quasi‐solid electrolyte with modified Li + solvation environment is developed. The unique design of Janus host assisted with the as‐formed aggregated ionic pairs contributes to a high‐performance solid electrolyte with superior safety, which greatly promotes the practical applications of solid‐state lithium batteries.